Ramsey method for Auger-electron interference induced by an attosecond twin pulse - Buth, Christian; Schafer, Kenneth (Physical review. A, Atomic, molecular, and optical physics, 2015)
We examine the archetype of an interference experiment for Auger electrons: two electron wave packets are launched by inner-shell ionizing a krypton atom using two attosecond light pulses with a variable time delay. This setting is an attosecond realization of the Ramsey method of separated oscillatory fields. Interference of the two ejected Auger-electron wave packets is predicted, indicating that the coherence between the two pulses is passed to the Auger electrons. For the detection of the interference pattern an accurate coincidence measurement of photo- and Auger electrons is necessary. The method allows one to control inner-shell electron dynamics on an attosecond timescale and represents a sensitive indicator for decoherence.
Gesehen am 30.10.2020